Impact of constant low gas pressure on cardiopulmonary parameters and surgical outcomes in extraperitoneal total nerve-sparing robot-assisted radical prostatectomy - Cochetti, Giovanni; Paladini, Alessio; Vitale, Andrea; Mearini, Matteo; Simonte, Rachele; Oliva, Francesco; Valeri, Davide; De Robertis, Edoardo; Mearini, Ettore (Frontiers in Surgery, 2026)
Traditionally, in extraperitoneal robot-assisted radical prostatectomy (EP-RARP), a pneumo-Retzius is obtained by using a CO2 insufflation pressure of 12–15 mmHg. However, EP surgery is associated with an increase in CO2 absorption and consequent hypercapnia and acidosis. This study aimed to compare the effect of low CO2 pressure (8 mmHg) with the conventional gas pressure in EP-RARP. We enrolled patients with low-risk prostate cancer who had undergone total nerve-sparing RARP using our PERUSIA (Posterior, Extraperitoneal, Robotic, Under Santorini, Intrafascial, Anterograde) technique. The exclusion criteria were the presence of chronic lung disease, a positive biopsy core from the anterior zone, or a shift to a transperitoneal approach. Cardiopulmonary parameters were measured at the induction of anesthesia (T0); at 5 (T1) and 60 (T2) minutes after starting CO₂ insufflation; and immediately after dorsal venous complex dissection before urethro-vesical anastomosis (T3). Data from 120 consecutive patients were retrospectively analyzed from a prospectively maintained database. Patients were divided into two groups based on the CO2 insufflation pressure (8 vs. 12 mmHg). No significant differences were detected in mean operative time, time required for trocar positioning, mean estimated blood loss, or complications between the two groups. The only significant difference was in the partial pressure of carbon dioxide, which was higher at T3 in Group 2 (p=0.005), with a consequent reduction in arterial pH. However, no significant difference (p = 0.44) was found regarding acidosis between the two groups at all timepoints. RARP has become a standard procedure in urological surgery for the treatment of localized prostate cancer. However, the CO2 insufflation required to create a surgical workspace may lead to cardiopulmonary complications, especially in patients with pre-existing respiratory conditions. This study compared the effects of a lower insufflation pressure (8 mmHg) vs. the standard pressure (12 mmHg) during EP-RARP. The findings suggest that using a low and constant pressure can reduce CO2 absorption into the bloodstream without increasing intraoperative or postoperative complications. This approach may expand eligibility for EP-RARP to include patients with chronic pulmonary diseases by enhancing the safety and tolerability of the procedure.